Water quality from wells in a tének community in the Huasteca Potosina, Mexico - Esparza-González, Jaqueline; Castillo-Pérez, Luis J.; Zavala-Cuevas, Diana; Carrillo-Inungaray, María Luisa; Carranza-Álvarez, Candy; Martínez Soto, Domingo (Ecosistemas y Recursos Agropecuarios, 2020)
El Tamarindo is a community located in the Tenek area of Ciudad Valles, San Luis Potosí, Mexico, where most of inhabitants consume and supply their basic needs with water from two shallow wells. The goal of this research was to analyze the physicochemical and microbiological characteristics, as well as identifying and quantifying the presence of metals in the mentioned water. Samplings were carried out in triplicate under dry, rainy, and post-rain seasons. The results showed high concentrations of total and fecal coliforms in both wells. Also, trace concentrations of cadmium, mercury, tin, lead, thallium, arsenic, zinc, copper, and nickel were found in the water, which can cause harm to human health. In conclusion, the water from the wells of this community does not have the quality required for human consumption. The water must be processed under purification methodologies previous to its consumption and use in domestic activities.